Chapter Textos y diálogos en diálogo: Barlaán y Josafat, de Lope - CRIVELLARI, DANIELE (Studi e saggi, 2021)
In this article I will study the hagiographic play Barlaán y Josafat, by Lope de Vega, from two different perspectives. On the one hand, I will analyze the dialogue between the two texts, as the comedia has a version transmitted by an autograph manuscript by Lope and another one transmitted through printed books and sueltas. On the other hand, I will focus my attention on the dialogues in the play, since they are useful to better understand the work of composition and preparation of the copy of the comedia by the playwright, as well as the company's work on the text.